Antara Tata Kelola Syariah dan Hukum Negara: Perspektif Siyāsah Syarʻiyyah tentang Integrasi Fiqih Bīʻah dalam Perlindungan Hutan Mangrove di Kabupaten Sinjai - Majid, Nurchaliq; Selvi, Selvi (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2026)
Mangrove forest protection requires not only effective state regulation but also the incorporation of religious values that strengthen environmental responsibility. From the perspective of Siyasah Syarʻiyyah, government policies aimed at promoting public welfare (maslahah), including environmental conservation, constitute an essential component of Sharia governance. This study analyzes the efforts of the Sinjai Regency Government to protect mangrove forests and examines the integration of Fiqh Biʻah into the existing legal protection framework from the perspective of Siyasah Syarʻiyyah. This study employed a qualitative case study approach. Primary data were collected through field observations, in-depth interviews, and documentation, while secondary data were obtained from statutory regulations, scholarly literature, and other relevant documents. The data were analyzed descriptively by integrating the perspectives of state law and Siyasah Syarʻiyyah. The findings reveal that the Sinjai Regency Government has implemented mangrove protection through legal regulations, the enforcement of administrative and criminal sanctions against environmental offenders, and the establishment of community-based environmental groups actively engaged in mangrove conservation. From the perspective of Fiqh Biʻah, these measures are consistent with Islamic principles that prohibit environmental destruction (fasad) and assign the state responsibility for safeguarding the public interest through environmental protection. The integration of state law and Islamic legal values has strengthened environmental governance while encouraging greater community participation in preserving mangrove ecosystems. Mangrove forest protection in Sinjai Regency demonstrates that integrating Fiqh Bīʻah into government environmental policies through the framework of Siyasah Syarʻiyyah contributes to a more effective and sustainable governance model by harmonizing state law with Islamic environmental ethics to achieve ecological sustainability and public welfare.